2012
DOI: 10.1111/tpj.12000
|View full text |Cite
|
Sign up to set email alerts
|

Versatile roles of Arabidopsis plastid ribosomal proteins in plant growth and development

Abstract: SUMMARYA lack of individual plastid ribosomal proteins (PRPs) can have diverse phenotypic effects in Arabidopsis thaliana, ranging from embryo lethality to compromised vitality, with the latter being associated with photosynthetic lesions and decreases in the expression of plastid proteins. In this study, reverse genetics was employed to study the function of eight PRPs, five of which (PRPS1, -S20, -L27, -L28 and -L35) have not been functionally characterised before. In the case of PRPS17, only leaky alleles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 69 publications
7
127
0
Order By: Relevance
“…The mutants mterf6-2 (SAIL_360_H09), mterf6-4 (SALK_098509), and ptac2 (GK_015F09) were identified in the SIGnAL database (Alonso et al, 2003), and mterf6-3 (SGT1851-3-3) was found in the database described by Parinov et al (1999). The mutant clb19-3 (SALK_123752; Chateigner-Boutin et al, 2008) has been described previously, as have prps17-1 and prpl24-1 (Romani et al, 2012) and rnr1-3 (Bollenbach et al, 2005). With the exception of mterf6-3 (which is a Landsberg erecta strain), all mutants are in the Col-0 background.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutants mterf6-2 (SAIL_360_H09), mterf6-4 (SALK_098509), and ptac2 (GK_015F09) were identified in the SIGnAL database (Alonso et al, 2003), and mterf6-3 (SGT1851-3-3) was found in the database described by Parinov et al (1999). The mutant clb19-3 (SALK_123752; Chateigner-Boutin et al, 2008) has been described previously, as have prps17-1 and prpl24-1 (Romani et al, 2012) and rnr1-3 (Bollenbach et al, 2005). With the exception of mterf6-3 (which is a Landsberg erecta strain), all mutants are in the Col-0 background.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…To quantify those reductions accurately, total RNA preparations of the wild type and mterf6-1 and mterf6-2 mutants grown on MS medium were analyzed with a Bioanalyzer, whereby 16S rRNA, 23S rRNA, and 18S rRNA levels were quantified as means for the plastid small and large and the cytosolic small ribosomal subunit, respectively. Total RNA preparations of the ribonucleotide reductase1-3 (rnr1-3) mutant (Bollenbach et al, 2005) and the chloroplast ribosomal mutants plastid ribosomal protein S17 (prps17-1) and plastid ribosomal protein L24 (prpl24-1; Romani et al, 2012) served as controls for altered rRNA accumulation (Supplemental Fig. S2).…”
Section: Impairment Of Mterf6 Affects Chloroplast Gene Expressionmentioning
confidence: 99%
“…6). Many of the nucleus-encoded components of the plastid ribosomes are essential for plant growth and development, since their absence results in diverse phenotypic effects, such as embryo lethality, paleness, and reduced overall sizes (Magnard et al, 2004;Asakura et al, 2012;Romani et al, 2012). The Arabidopsis TF CHLOROPLAST IMPORT APPARATUS2 (CIA2) was shown to up-regulate the expression of genes encoding chloroplast ribosomal proteins to accomplish the high protein demands of chloroplasts ).…”
Section: Protein Synthesis Is Negatively Correlated To Leaf Growthmentioning
confidence: 99%
“…Several studies focusing on the identification of nuclear genes essential for embryo development (Meinke et al, 1994;Bryant et al, 2011;Candela et al, 2011;Romani et al, 2012;Savage et al, 2013) have noted the high frequency of such genes that encode products presumably involved in plastid translation. It is becoming clear that the essential function provided by plastid translation during embryogenesis is the synthesis of the product of the accD gene, encoding the catalytic subunit of the plastid acetyl-CoA carboxylase (required for malonyl-CoA production for fatty acid biosynthesis).…”
mentioning
confidence: 99%